Characterisation of the genomic landscape of CRLF2‐rearranged acute lymphoblastic leukemia. Issue 5 (18th January 2017) - Russell, Lisa J.; Jones, Lisa; Enshaei, Amir; Tonin, Stefano; Ryan, Sarra L.; Eswaran, Jeyanthy; Nakjang, Sirintra; Papaemmanuil, Elli; Tubio, Jose M. C.; Fielding, Adele K.; Vora, Ajay; Campbell, Peter J.; et al.
Abstract: Deregulated expression of the type I cytokine receptor, CRLF2, is observed in 5–15% of precursor B‐cell acute lymphoblastic leukaemia (B‐ALL). We aimed to determine the clinical and genetic landscape of those with IGH‐CRLF2 or P2RY8‐CRLF2 ( CRLF2 ‐r) using multiple genomic approaches. Clinical and demographic features of CRLF2 ‐r patients were characteristic of B‐ALL. Patients with IGH‐CRLF2 were older (14 y vs. 4 y, P < .001), while the incidence of CRLF2 ‐r among Down syndrome patients was high (50/161, 31%). CRLF2 ‐r co‐occurred with primary chromosomal rearrangements but the majority (111/161, 69%) had B‐other ALL. Copy number alteration (CNA) profiles were similar to B‐other ALL, although CRLF2 ‐r patients harbored higher frequencies of IKZF1 (60/138, 43% vs. 77/1351, 24%) and BTG1 deletions (20/138, 15% vs. 3/1351, 1%). There were significant differences in CNA profiles between IGH‐CRLF2 and P2RY8‐CRLF2 patients: IKZF1 (25/35, 71% vs. 36/108, 33%, P < .001), BTG1 (11/35, 31% vs. 10/108, 9%, P =.004), and ADD3 deletions (9/19, 47% vs. 5/38, 13%, P =.008). A novel gene fusion, USP9X‐DDX3X, was discovered in 10/54 (19%) of patients. Pathway analysis of the mutational profile revealed novel involvement for focal adhesion. Although the functional relevance of many of these abnormalities are unknown, they likely activate additional pathways, which may represent novel therapeutic targets.